Evaluation of an Experimental Virtual Learning Environment of Winemaking for Middle School and College Students in Chile - Claudio Fredes; Sergio Espinoza (Universidad Nacional, Costa Rica, 2018)
BITWINE is a virtual learning environment (VLE) that was aimed to develop work competencies in the winemaking industry based on Chilean winemaking work standards. This paper analyzed the learning of the winemaking process as well as the likeability and functionality of BITWINE for university and technical school students. The learning with BITWINE was tested through quasi-experimental tests for groups control (with BITWINE) and experimental (without BIWINE) with written assessment. Furthermore, functionality and likeability perceptions, obtained through written surveys, are analyzed and discussed. The results showed that those students who used BITWINE improved their learning. The perception of BITWINE likeability demonstrated that it was well designed. The studied VLE also contributed to teach how to work with appropriate norms of traceability, hygiene and work safety. However, although BITWINE was quite appreciated as an e-learning tool, it still requires better information and communications technology conditions to be functional.